A vertical structure photodetector based on all‐inorganic perovskite quantum dots. Issue 1 (3rd December 2019) - Yan, Shikai; Li, Qing; Zhang, Xu; Tang, Sheng; Lei, Wei; Chen, Jing
Abstract: In this work, the vertical structure photodetector based on CsPbBr3 quantum dots (QDs) with a structure of indium tin oxide (ITO)/zinc oxide (ZnO)/CsPbBr3 QDs/Au is reported. In this device, CsPbBr3 QDs film works as the light‐harvesting layer, and ZnO QDs film acts as the electron transport channel, which can extract the electron efficiently and improve the quality of CsPbBr3 QDs film. As a result, the on/off ratio, detectivity and rise time (decay time) of CsPbBr3 /ZnO hybrid photodetector are measured to be 2.4 × 10 6, 2.25 × 10 11, and 62 milliseconds (82 ms) under 0‐V bias. This work inspires the development of vertical structure photodetectors based on the all‐inorganic perovskite QDs. Abstract : We report a vertical structure photodetector based on CsPbBr3 quantum dots (QDs) with a structure of indium tin oxide (ITO)/zinc oxide (ZnO)/CsPbBr3 QDs/Au. The photodetector shows high performance at low bias, which makes the device energy efficient. Our device also shows good stability and durability.